PERUBAHAN POLA KONSUMSI PANGAN RUMAH TANGGA AKIBAT PENCABUTAN SUBSIDI LISTRIK (STUDI KASUS DI KOTA PRABUMULIH SUMATERA SELATAN) - Siska Alfiati; Rona Anggrainie (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2018)
The government's policy to revoke household electricity subsidies will have a direct impact on household expenditure, which in turn will also affect food consumption patterns. The purpose of this research is analyze changes in household food consumption patterns as a result of the removal of electricity subsidies in Prabumulih City. This research was conducted in the City of Prabumulih, South Sumatra in March 2018 September 2018. The method used in this study was a survey method by taking 100 households from a population of 56,003 households that had 900 VA of electric power taken in a simple random sampling. The results showed that there were significant differences between household food consumption patterns before and after the removal of electricity subsidies.